Onset of Mechanochromic Response in the High Strain Rate Uniaxial Compression of Spiropyran Embedded Silicone Elastomers. Issue 1 (21st October 2020) - Shannahan, Logan S.; Lin, Yangju; Berry, James F.; Barbee, Meredith H.; Fermen‐Coker, Müge; Craig, Stephen L.
Abstract: The molecular processes that accompany dynamic mechanical response to large deformations at high strain rate (≈1000 s −1 or higher) underlie the early stages of damage in materials, but understanding of material response in this regime is typically limited to macroscopic constitutive equations. Here, spiropyran mechanophores are embedded in very short, stress‐bearing strands in silicone elastomers, and their mechanochromic response to uniaxial compression is explored in a Split Hopkinson Pressure (or Kolsky) Bar. At strain rates of 1000 s −1, the onset of mechanochromism occurs at lower strains, but higher stresses, than in the same materials under quasi‐static loading. Similar to quasi‐static loading, however, a negligible effect of mechanophore structure on the critical strain for colorimetric onset is observed. The results suggest that nonequilibrium, inhomogeneous local tension distributions in the elastomers lead to greater stress in individual strands than at the same strains under equilibrium loading, but that within the regions of force concentration, mechanochromic onset is determined primarily by a limiting local strain threshold. Abstract : The onset of mechanochromism in spiropyran (SP) functionalized silicone elastomers under high strain rate uniaxial compression occurs at lower strain but higher stress than in the same samples under quasi‐static loading. No dependence of strain onset on mechanophore structure is observed across four SP derivatives.